Curcumin and Its Analogs in Non-Small Cell Lung Cancer Treatment: Challenges and Expectations - Chunyin Tang; Jieting Liu; Chunsong Yang; Jun Ma; Xuejiao Chen; Dongwen Liu; Yao Zhou; Wei Zhou; Yunzhu Lin; Xiaohuan Yuan (Biomolecules, 2022)
Researchers have made crucial advances in understanding the pathogenesis and therapeutics of non-small cell lung cancer (NSCLC), improving our understanding of lung tumor biology and progression. Although the survival of NSCLC patients has improved due to chemoradiotherapy, targeted therapy, and immunotherapy, overall NSCLC recovery and survival rates remain low. Thus, there is an urgent need for the continued development of novel NSCLC drugs or combination therapies with less toxicity. Although the anticancer effectiveness of curcumin (Cur) and some Cur analogs has been reported in many studies, the results of clinical trials have been inconsistent. Therefore, in this review, we collected the latest related reports about the anti-NSCLC mechanisms of Cur, its analogs, and Cur in combination with other chemotherapeutic agents via the Pubmed database (accessed on 18 June 2022). Furthermore, we speculated on the interplay of Cur and various molecular targets relevant to NSCLC with discovery studio and collected clinical trials of Cur against NSCLC to clarify the role of Cur and its analogs in NSCLC treatment. Despite their challenges, Cur/Cur analogs may serve as promising therapeutic agents or adjuvants for lung carcinoma treatment.